Gender differences: Students’ science process skills based on gender homogeneous class - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Ricky Purnama Wirayuda (Universitas Negeri Yogyakarta, 2022)
This study was aimed to describe the ability of students’ science process skills based on indicators, and to find out the significance in students’ science process skills based on gender homogeneous classes. This is qualitative research with descriptive and inferential statistical approaches. This research was conducted at SMPN 9 Muaro Jambi with a population of all eighth-grade students, and the research sample was 60 students. Determination of the sample was done by random sampling. The whole sample was divided into two groups based on their gender. The instrument used in this study was a science process skill observation sheet. The data were then analyzed using descriptive statistics. The results obtained by the science process skills of the students are in the good category based on basic and integrated science process skills. The value is greater than 50% on each indicator. There is no significant differences between the science process skills of male and female students.